Supported employment for adults with severe mental illness - Peter Huxley (Cochrane Database of Systematic Reviews, 2013)
This is an updated Cochrane Review originally published in the 1990s of which I was an originator, data analyst and co-author with Crowther, Marshall and Bond. I was trained for this systematic review by the Schizophrenia group in Oxford.The latter two authors plus myself and the principal author in Japan updated the original review. Both reviews confirm that the supported employment model for people with serious mental health problems is superior to the train and place and similar methods.